A household survey of maternal and child health in the Mount Frere Health District, Eastern Cape - Irlam, James (Institute of Infectious Disease and Molecular Medicine, 2018)
A cross-sectional household survey of maternal and child health was conducted in the Mount Frere health district of the Eastern Cape in August / September 1997. The aim was to describe key aspects of maternal and child health to inform the planning activities of the District Health Management Team (DHMT). A participatory process was followed, in order to develop research capacity within the district, and to facilitate interaction between health workers and the community. Methods: Structured questionnaires were used by local research trainees to gather data from each household on: • household demographics; • deaths in household since April 1994; • household access to water and sanitation; • children under five years; • children aged 5 to 15 years; • deliveries in the past 12 months; • knowledge of prevention and transmission of HIV/AIDS. Focus group discussions around the key findings were conducted with community members and clinic nurses to provide a qualitative component. Results: A high proportion of children under the age of 16, high household density, high unemployment, migrant labour, and absent mothers, are some of the defining demographic characteristics which affect the status of maternal and child health in the district. Access to health services is constrained by distance, lack of transport, and poor roads. Registration of births and deaths is poor, and the crude birth and death rates were found to be significantly higher than the " official" provincial rates. Tuberculosis, diarrhoea, trauma and homicide are notable features of the overall mortality profile, although the majority of deaths were classified "ill-defined / unknown". Diarrhoea and pneumonia accounted for half of all infant deaths. Eight out of ten deaths due to diarrhoea in under-fives occurred at home, but knowledge and use of oral rehydration solution is poor. Access to clean drinking water and sanitation is a major concern, with almost three quarters of homes using unprotected sources, a third more than 30 minutes' walk from the nearest source, and a half having no toilet. Areas of the district with particularly poor environmental health indicators were identified. Immunisation coverage among children 1-4 years is poor. Coverage for all vaccines except BCG falls well short of the national target of 90%, and fewer than 1 in 3 children was fully immunised with valid doses at the age of one year. Long intervals between doses and a high "dropout" rate between subsequent doses was observed. The road to health card (RTHC) could be produced for just over a half of under-five children. The proportion of home deliveries is high (45%), and traditional birth attendants (TBAs) therefore play an important role in this community. Nine out of ten mothers had attended antenatal clinic at least once, but almost half reported receiving no tetanus toxoid and no WR test for syphilis during their antenatal visits. More than a half of all mothers was using no family planning method at the time of the survey. Almost all 15-49 year-olds had heard about HIV/AIDS, but one in five did not know how HIV is transmitted, and a third did not know how it could be prevented. Recommendations: A detailed set of recommendations with action points for the DHMT was developed in a district workshop around the following key issues: 1. Improving access to health care, including road access, mobile clinic coverage, and waiting facilities for expectant mothers. 2. Promoting health in the community, by means of integration of health promotion into all health programmes, and more involvement of communities. 3. Improving the quality of care in the existing health facilities and services, including minimising missed opportunities for immunisation, and promoting home-made oral rehydration (sugar-salt) solution. 4. Improving the district health information system, especially the registration of vital events, and the provision of feedback to district health managers. 5. Identifying areas of further research, including the reasons for home deliveries, management of diarrhoea at home, and the use of traditional healers. Conclusion: The participatory research process that was used has helped to build research capacity in the district, to provide a deeper insight into community health problems, to highlight the value of health workers listening to the people they serve, to further collaboration between the disciplines, and to develop specific action plans. This is a process that should be followed in all research conducted in health districts.